Polymorphism Control of Layered MoTe2 through Two-Dimensional Solid-Phase Crystallization - Huang, Jyun-Hong; Hsu, Hao-Hua; Wang, Ding; Lin, Wei-Ting; Cheng, Chun-Cheng; Lee, Yao-Jen; Hou, Tuo-Hung (Scientific reports, 2019)
Two-dimensional (2D) molybdenum ditelluride (MoTe 2 ) exhibits an intriguing polymorphic nature, showing stable semiconducting 2H and metallic 1T′ phases at room temperature. Polymorphism in MoTe 2 presents new opportunities in developing phase-change memory, high- performance transistors, and spintronic devices. However, it also poses challenges in synthesizing homogeneous MoTe 2 with a precisely controlled phase. Recently, a new yet simple method using sputtering and 2D solid-phase crystallization (SPC) is proposed for synthesizing high-quality and large-area MoTe 2 . This study investigates the polymorphism control of MoTe 2 synthesis using 2D SPC. The Te/Mo ratio and oxygen content in the as-sputtered films correlate strongly with the final phase and electrical properties of SPC MoTe 2 . Furthermore, the SPC thermal budget may be exploited for stabilizing a deterministic phase. The comprehensive experiments presented in this work demonstrate the versatile and precise controllability on the MoTe 2 phase by using the simple 2D SPC technique.